SUNTER RIVER DIVERSION PLANNING ON THE CONSTRUCTION OF JAKARTA-BANDUNG HIGH-SPEED RAILWAY IN HALIM PERDANA KUSUMA EAST JAKARTA - Fern Anisyha Putri, Ratashya
One of the National Strategic Projects is Jakarta-Bandung High-Speed Railway Project, which is built from Halim Station in East Jakarta to Tegalluar Station in Bandung Regency. The railway at Halim Perdana Kusuma Area coincides with the Sunter River, it needs to be relocated so that the construction does not interfere with the river flow. Sunter River diversion is planned along 661 m of the existing river, which must be diverted along 784 m. In accordance with the applicable regulations on river channel diversion, it is necessary to plan the channel by considering the river diversion area, channel volume, and channel stability. Planning is done by analyzing the existing river conditions and designing the dimensions of the river diversion with a stable channel. Channel dimensions are planned with a 100 year return peak flood period of 313.60 m3/s. Channel designed to three shapes rectangular, trapezoidal, and compound. Using Analytical Hierarchy Process Method, a rectangular shape with a width of 23 m, a depth of 4 m, and using concrete sheet pile with a depth of 12 m was selected. To reduce velocity and scour in the channel, two 0.4 m drop structures were used and the channel slope was flattened to 0.001. The rectangular channel with modified riverbed can reduce the maximum scour by 36.8% compared to before the modification of the riverbed.